To Whom Does Destination Anthropomorphism Appeal? Power and Perceived Control. (April 2023) - Chan, Eugene; Gohary, Ali
Anthropomorphism refers to the assignment of human-like traits and characteristics to non-human objects. In the tourism sector, destinations can be anthropomorphized. In this investigation, we explore potential travelers' power as a factor that predicts to whom destination anthropomorphism appeals. Because anthropomorphism facilitates individuals' perceived control, which individuals low on power lack but want to regain, we hypothesize in the current research that destination anthropomorphism would appeal more to travelers low (vs. high) on power. The higher perceived control manifests in travel behavior in the form of fewer perceived risks while traveling. We observe that powerless (vs. powerful) participants perceive greater control (Experiment 2) and fewer risks while traveling (Experiment 3) when the destination is anthropomorphized, explaining their higher travel intentions (Experiments 1–3). Our results suggest that whether or not to use anthropomorphism in destination advertising needs to consider potential travelers' power.